Menjaga Keseimbangan Alam Melalui Kearifan Lokal Tradisi Panggoba dalam Pembangunan Pertanian Berkelanjutan - Andi Sulia Sudirman; Andrias Andrias; Tahir Tahir; Septianto Aldiansyah (Jurnal Penelitian Pendidikan Geografi, 2025)
Local wisdom plays a crucial role in maintaining ecological balance while supporting sustainable agricultural practices. This study aims to identify the practices of the Panggoba tradition among farming communities in Leboto Village, North Gorontalo. The research employed a qualitative method with an ethnographic approach through in-depth interviews, participant observation, and document analysis. The findings reveal that the Panggoba tradition, which includes determining planting schedules based on indigenous astronomy and performing the Rotan Tikus ritual for pest control is still preserved by some farmers. This tradition contributes to regulating planting seasons, reducing pest control costs, and maintaining ecological balance. However, modernization and climate change have reduced the intensity of its practice. The study highlights that the Panggoba local wisdom carries ecological, social, and economic values that remain highly relevant for sustainable agricultural development.